Math
posted by Janae on .
Simplify the expressions
(ab^2c)^1 / a^8b^2c^4b^3

(ab^2c)^1 = a^1b^2c^1
a^8b^2c^4b^3 = a^8b^5c^4
a^1b^2c^1 / a^8b^5c^4 = a^9b^7c^3
= c^3 / a^9b^7 
ok i get it now.
for this question..
3square root of 1/2x+1 +2=5
the +2=5 is out of the square root.
so do i get rid of the square root first or subtract 2 from 5 
do the reverse of PEMDAS
3√1/(2x+1) + 2 = 5
3/√(2x+1) = 3
1/√(2x+1) = 1
1 = √(2x+1)
squaring yields
1 = 2x+1
0 = 2x
x = 0
check:
3/√1 + 2 = 5
yes
Rather a poor exercise, imho